An aggregate transport demand model for import and export flow simulation - Nuzzolo, Agostino; Crisalli, Umberto; Comi, Antonio (Transport, 2015)
This paper presents a system of models for the estimation of international (import/export) freight flows through a partial share approach. It allows us to simulate attraction, production, distribution and modal split for the estimation of modal Origin-Destination matrices in quantities. Aiming at predicting long term effects for strategic planning, the modelling system has been specified through easy-to-capture variables represented by level-of-service attributes and aggregate socio-economic variables. The calibration was carried out by using a set of available data in Italy that allowed us to consider import/export flows for different freight types given by the aggregation of classes provided by European NST/R classifications.First published online: 25 Oct 2013